ANALISIS PENILAIAN SAHAM PT BANK ARTHA GRAHA INTERNASIONAL Tbk. PASCA KEBIJAKAN INSENTIF PAJAK PER 31 DESEMBER 2010 - , Nasrah Mawardi, S.E. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is aimed to estimate the intrinsic stock value of PT Bank Artha Graha Internasional ,Tbk. after the 5 percen tax incentif policy per 31 December 2010.This research is done by using dicounted cashflow and relative valuation methods.Theresearchbecomes interestingbecauseof tax incentif policy is being issued, it is expected for the stock value to increases. However there are differences between the market and the expected value. This phenomenon encourage the writer to analyzed the stock value of PT Bank Artha Graha using the methods above. Thedatausedinthisresearchconsistsofitsfinancialreport,annualreport,comparable ecompanyâsfinancialreport,comparablecompanyâsstockprice,riskfreerate,andothersuppo rtingdata.TheanalysisusedisDCFmethodswhichgo withthefollowingsteps:salesorearningsprojectionanalysis,financialstatement projection,freecashflowprojection,discountratedeterminationand terminal value estimation. Relativevaluation method was started by determining comparablecompanyontheindustry,followedbychoosinganddeterminingthemultipleswic hwillbeusedtoconversebookvalueonrelevantvariableonPT Bank Artha Graha Internasional Tbk. Tobeestimationofmarketvalueofequity.Themultiplesusedare:PriceEarningRatio(PER)an dPricetoBookValue(PBV).Theresultoftheresearchshowsthatitsintrinsicvalueofthe stocks isRp140,20.Theequityvalue,basedonDCFmethodisRp151,88 andonrelativevaluationmethod Rp 128,52 (PER=Rp145,34andPBV=Rp 136,92) and(Price to Sales = Rp 100,49)